Integrated versus Segmented Markets: Implications for Export Pricing and Welfare - Raphael Becker; Sergey K. Nigai; Tobias Seidel (Center for Economic Studies and Ifo Institute (CESifo), 2020)
This paper challenges the common assumption of market segmentation in international trade. To analyze export entry and pricing decisions of firms in integrated vs. segmented markets, we develop a novel tractable approach based on stochastic export costs that allows us to compare firm-level and aggregate outcomes under arbitrary market interdependence. We find that allowing for potential re-exporting arbitrage between countries imposes constraints on export prices of firms and has first-order implications for trade and welfare.
Keywords: F12; F13; F14; F15; 330; market segmentation; pricing constraints; gains from trade